Chronic Suppurative Lung Disease in Children: Definition and Spectrum of Disease - Redding, Gregory J.; Carter, Edward R. (Frontiers in Pediatrics, 2017)
Suppurative lung disease by definition is characterized by accumulation of pus in response to persistent infection and is compartmentalized within the lung and airways. Examples of chronic suppurative lung disease include lung abscess, bronchiectasis and more recent entities of protracted bacterial bronchitis and chronic suppurative lung disease, similar to but not diagnostic of bronchiectasis. Children are predisposed to suppurative lung disease who have compromised pulmonary host defenses, ongoing aspiration of upper airway bacteria, inhaled irritant exposure producing hypersecretion in the airways, and recurrent lung/airway injury most often due to viral infections. Global risk factors include acute pneumonia, tobacco and biomass burning, malnutrition, tuberculosis, and HIV infections. Global distribution of these risks factors suggest a highest prevalence would occur in Subsaharan Africa and Asia, including India and China. However, prevalence rates for chronic suppurative lung disease in children have not been reported in these high risk areas. Better epidemiology is needed to assess the global burden of chronic suppurative lung disease in children.